2018
DOI: 10.5430/crim.v5n3p13
|View full text |Cite
|
Sign up to set email alerts
|

Lambl’s excrescences and a review of therapeutic strategies

Abstract: Background: Lambl’s excrescences (LEx) are thin, filiform structures that arise on the lines of closure of heart valves. Although rare, we have come across various case reports in the literature describing thromboembolic events associated with LEx. We report the case of a 63-year-old female who presented with TIA-like symptoms and was found to have a LEx on the aortic side of native aortic valve. We conducted a comprehensive literature review with emphasis on different therapeutic strategies utilized to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is reasonable to offer surgical valve replacement after second CVA related to LE as the recurrence rate of CVA is high [15]. In a patient with poor medical compliance, surgical excision and valve replacement may be a better option for TIA/CVA symptoms secondary to LE, given the bleeding risk on antiplatelet/anticoagulation therapy [21]. A summary of the current practices in the management of LE is schematically represented in Figure 1.…”
Section: Treatmentmentioning
confidence: 99%
“…It is reasonable to offer surgical valve replacement after second CVA related to LE as the recurrence rate of CVA is high [15]. In a patient with poor medical compliance, surgical excision and valve replacement may be a better option for TIA/CVA symptoms secondary to LE, given the bleeding risk on antiplatelet/anticoagulation therapy [21]. A summary of the current practices in the management of LE is schematically represented in Figure 1.…”
Section: Treatmentmentioning
confidence: 99%
“…In subsequent pathologic series of normal valves, a 70% to 90% prevalence of LEx was reported, predominantly on the MV (70% to 85%), followed by the AV (62% to 90%) and the right-sided valves (8% to 20%). 9 Recently, Osorio et al 10 analyzed 33 cases of LEx, and reported the affected valve was AV in 75% (25/33), followed by MV in 17% (6/33) and pulmonary valve in 2.8% (1/33). Salah et al 11 analyzed the cases published from 1981 to 2018; in that series, the affected valve was AV in 89% and MV in 7%, with one case in the pulmonary valve.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis of vegetations includes thrombus, hypoattenuated leaflet thickening (HALT), fibroelastoma, Lambl's excrescencies, and non-bacterial endocarditis (NBTE) [58][59][60][61][62]. Thrombus is irregular soft tissue lesion attached to the leaflets, sewing ring, or both, predominantly to the side of higher pressure [58].…”
Section: Infective Endocarditis Related Lesionsmentioning
confidence: 99%
“…Fibroelastoma are pedunculated lesions attached to the leaflet, rarely causing valve dysfunction or emboli due to thrombi adherence or disintegration [60]. Lambl's excrescences are thinner filiform lesions that arise in commissural valve zones [61]. NBTE appears as small irregular lesions, commonly affects left-sided valves and is associated with malignancy, hypercoagulable states, and autoimmune disease (Libman-Sacks endocarditis).…”
Section: Infective Endocarditis Related Lesionsmentioning
confidence: 99%